Question

Sol. ( (1) sec theta+tan theta=sqrt{3} )
( because sec ^{2} theta-tan ^{2}=1 )
( Rightarrow(sec theta-tan theta)(sec theta+tan theta)=1 )
( Rightarrow sec theta-tan theta=frac{1}{sqrt{3}} )
By subtracting (ii) from (i)
( Rightarrow sec theta+tan theta-sec theta+tan theta Rightarrow sqrt{3}-frac{1}{sqrt{3}} )
( 2 tan theta=frac{3-1}{sqrt{3}} )
( Rightarrow tan theta=frac{1}{sqrt{3}}=tan 30^{circ} )
( Rightarrow theta=30^{circ} )
( therefore tan 3 theta=tan 3 times 30^{circ}=tan 90^{circ}= ) undefined

# Ex. 1. If sece + tane = 73 (0° se s 90°) then tan 30 is (1) undefined (2) TB (3) T2 (4) 13

Solution